Smith-Purcell effect as resonant diffraction radiation - Potylitsyn A. P. Alexander Petrovich (1998, 1998)
The radiation of ultrarelativistic charged particle passing near a grating (Smith-Purcell radiation (SPR)) has been considered on the basis of a simple physical model, where SPR is treated as the resonant diffraction radiation (RDR). The apparent analogy between RDR and a well known resonant transition radiation has been used. The results have been compared with those obtained via other approaches. For an ultrarelativistic case it has been shown that the SPR intensity for a grating designed from strips separated by vacuum gaps sufficiently exceeds the one for traditional grating made up by a periodically deformed continuous surface.